Product Legalization Literacy in The Framework of Increasing Sales in MSMEs (Case Study : BUMDesa Kuala Alam) - Desi Rama Diana; Wan Junita Raflah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The main goal of the project to be achieved in this final project is to create or organize a seminar is to provide an understanding of the legality literacy of a product in can carry out the process of making product legality to MSMEs business owners so that it thereby increasing human insight by following applicable regulations, with the background of problem namely in BUMDesa Kuala Alam which still does not have legal product legality as a whole. as for the participants who attended this activity amounted to 100 people consisting of 13 business people and 87 people from Students of State Polytechnic Bengkalis the process involved finding and determining the criteria for sponsors and speakers, knowing the planning and realization of the promotion budget, knowing the obstacles that occur, looking for solutions to the obstacles ancountered and evaluating seminar activities through feedback from participants. This final project uses 4 (four) methods consisting of project preparation plans, project implementation plans, accomplishment plans and project reporting plans. The results of the initial for this project seminar are the implementation product Legalization Literacy in MSMEs BUMDesa Kuala Alam in increase sales. awareness of business actors arises because they know the important role of halal legality in a product. then it can be seen that several MSMEs products have successfully carried out the legality process which has been assisted by students of the bengkalis state polytechnic as a contact person between business actors and the Bengkalis Chamber of Commerce and Industry institution, namely candied marmalade products, nipah sugar and nira nipah.